Height, weight, Body Mass Index, and age in beach volleyball players in relation to level and position - Palao, J. M.; Gutierrez, D.; Frideres, J. E. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: This study tried to find out the height, weight, Body Mass Index (BMI), and age of peak performance beach volleyball players with regard to their level of play and their role. Methods: The men's and women's pairs that classified in the World Tour and in the Olympic Games during seasons 2000-2006 were analyzed (625 males and 617 females). A descriptive, correlational, and longitudinal design was used. The variables studied were: height, weight, age, BMI, level (World Tour ranking), and player role (blocker, defense specialist, or no specialization). The data were obtained from the webpage of the International Federation of Volleyball. Results: The average characteristics for males were 1.93 m, 88-89 kg, a BMI of 23.8-24.1, and an age range of 29-31 years, and for females, they were 1.77-1.79 m, 66-68 kg, a BMI of 19.2-21.1, and an age range of 27-29 years. Conclusion: Beach volleyball players are older and have smaller anthropometric characteristics when compared to indoor volleyball players. Male players present similar values for age and height across rankings. For both genders, with regard to weight and BMI, the higher the level, the larger the value. For women, the players at a higher level presented higher values of age, height, weight, and BMI. With regard to role, the blocking specialists were taller than the defense specialists. The pairs that share the blocking and defense responsibilities have intermediate values.